THE STATUS AND RIGHTS OF CITIZENS IN THE PERSPECTIVE OF THE INDONESIAN CONSTITUTION: AN ANALYSIS OF THE 1945 CONSTITUTION - H Bambang Yuniarto; Nazwa Aulia Fajrin; Nurul Amanah; Muhamad Ferdiansyah; Salsa Nabila; Selli Rahmawati (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study aims to analyze the status and rights of citizens from the perspective of the Indonesian Constitution, with a particular focus on the provisions stipulated in the 1945 Constitution. The primary issue addressed in this research is the gap between constitutional guarantees of citizens’ rights especially the right to education and the realities encountered in practical implementation. Although the 1945 Constitution provides a strong legal foundation through Articles 27–34 and 28A–28J, various challenges such as unequal access to education, low legal literacy, and limited institutional capacity continue to hinder the fair and equitable fulfillment of citizens’ rights. This research employs a literature study method by reviewing constitutional documents and scholarly journal articles related to the protection of citizens’ fundamental rights. The findings indicate that ensuring the realization of citizens’ rights, particularly in the context of Islamic education, requires institutional strengthening, enhanced teacher competence, and the integration of constitutional and human rights values into Islamic Religious Education curricula. Accordingly, this study contributes to the development of knowledge and professional practices in Islamic education that are just, inclusive, and aligned with constitutional mandates.